2018
DOI: 10.1038/s41598-017-18188-y
|View full text |Cite
|
Sign up to set email alerts
|

Methylation in Mycobacterium tuberculosis is lineage specific with associated mutations present globally

Abstract: DNA methylation is an epigenetic modification of the genome involved in regulating crucial cellular processes, including transcription and chromosome stability. Advances in PacBio sequencing technologies can be used to robustly reveal methylation sites. The methylome of the Mycobacterium tuberculosis complex is poorly understood but may be involved in virulence, hypoxic survival and the emergence of drug resistance. In the most extensive study to date, we characterise the methylome across the 4 major lineages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 21 publications
(38 reference statements)
9
66
0
Order By: Relevance
“…In the absence of cation binding and thiol redox switch, the mode of transcriptional regulation of Rv0081 in response to hypoxic conditions therefore remains enigmatic. Based on previous studies we can hypothesize that under hypoxic conditions, the Rv0081 might get post‐translationally modified to alter its DNA‐binding ability by phosphorylation , acetylation , methylation or modulation by formylation . First, to check the possibility of phosphorylation of Rv0081, three Serines which are postulated to be involved in base‐recognition become excellent candidates to test this hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of cation binding and thiol redox switch, the mode of transcriptional regulation of Rv0081 in response to hypoxic conditions therefore remains enigmatic. Based on previous studies we can hypothesize that under hypoxic conditions, the Rv0081 might get post‐translationally modified to alter its DNA‐binding ability by phosphorylation , acetylation , methylation or modulation by formylation . First, to check the possibility of phosphorylation of Rv0081, three Serines which are postulated to be involved in base‐recognition become excellent candidates to test this hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DNA‐binding properties of Rv0081 might be metal independent. In Mtb, metal‐independent DNA binding is regulated by either thiol switch or post‐transcriptional modifications, such as phosphorylation , acetylation or methylation and we can postulate one or combination of such mechanisms regulates the activity of Rv0081. With the emerging significance of Rv0081 in dormancy and our own observation of its indirect dependence on GroEL , we have determined the crystal structure of Rv0081 and identified the possible molecular basis for binding of Rv0081 to its cognate DNA element.…”
mentioning
confidence: 99%
“…M. tuberculosis encodes three known DNA methyltransferases (MTases), MamA, MamB, and HsdM, which each target a different sequence motif for N6-adenine methylation ( Shell et al, 2013 ; Zhu et al, 2016 ). Previous studies have shown that loss-of-function (inactive) variants in these genes are common, and often associate with lineage ( Phelan et al, 2018 ; Zhu et al, 2016 ). These minor differences in genotype result in radically different methylomes, potentially explaining the phenotypic variation observed between lineages ( Phelan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that loss-of-function (inactive) variants in these genes are common, and often associate with lineage ( Phelan et al, 2018 ; Zhu et al, 2016 ). These minor differences in genotype result in radically different methylomes, potentially explaining the phenotypic variation observed between lineages ( Phelan et al, 2018 ). However, these studies examined only a handful of isolates from each lineage of the Mycobacterium tuberculosis complex (MTBC), included few or no resistant isolates, and did not directly examine kinetics at each motif, relying instead on the motifs identified from single-molecule, real-time sequencing (SMRT-sequencing) software to classify isolates as lacking methylation of a motif entirely.…”
Section: Introductionmentioning
confidence: 99%
“…Three completed L5 genomes from clinical isolates, all sequenced with the PacBio SMRT technology, were analyzed. One genome was from a Benin isolate (PcbL5Ben; sequenced in this study), one from an isolate from The Gambia (PcbL5Gam, WBB1453_11-00429-1) (Phelan et al 2018), and one from Nigeria (PcbL5Nig, WBB1454_IB091-1) (Phelan et al 2018). These genomes are also from disparate parts of the L5 diversity, representing a broad range of L5 sub-lineages, as were recently defined (Coscolla et al 2020).…”
Section: Genomesmentioning
confidence: 90%